Dinosaurs before dark - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1992)
Eight-year-old Jack and his younger sister Annie find a magic tree house, which whisks them back to an ancient time zone where they see live dinosaurs.
Book Links (A.L.A.).
Horn Book.
School Library Journal.
3.3
3-6
Keywords: Annie (Fictitious character : Osborne) -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Jack (Fictitious character : Osborne) -- Juvenile fiction; Magic -- Juvenile fiction; Time travel -- Juvenile fiction; Tree houses -- Juvenile fiction; Annie (Fictitious character : Osborne) -- Fiction; Dinosaurs -- Fiction; Jack (Fictitious character : Osborne) -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Annie (Fictional character : Osborne) -- Fiction; Dinosaurs -- Fiction; Jack (Fictional character : Osborne) -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tree houses -- Fiction